Modele matematyczne w fizyce współczesnej a pdstawowe problemy ontologii czasoprzestrzeni - Gos, Maciej (Filozofia Nauki, 1996)
Assuming that formulation of General Theory of Relativity gave rise to the attempts to formulate uniform field theory of matter, it must be emphasised that the work that inquired most deeply into its consequences for spacetime ontology and, moreover, for general ontology of physics that resulted from analysis of new physical theories, was H. Weyl's „Space Time Matter”.